Heat transfer enhancement and development of correlation for turbulent flow through a tube with triple helical tape inserts - Bhuiya, M.M.K.; Ahamed, Jamal Uddin; Chowdhury, M.S.U.; Sarkar, M.A.R.; Salam, B.; Saidur, Rahman; Masjuki, Haji Hassan; Kalam, M.A. (Elsevier, 2012)
Influence of triple helical tapes inserted for turbulent flow through a tube on heat transfer enhancement was studied experimentally. The triple helical tapes made of mild steel with different helix angles, alpha = 9 degrees, 13 degrees, 17 degrees, and 21 degrees were examined for Reynolds number ranging from 22,000 to 51,000. The experiment showed that the Nusselt number, effectiveness and friction factor for the inserts were found to be up to 4.5, 3.45 and 3.0 times, respectively, over the plain tube. The highest enhancement efficiency achieved was 3.7 for the inserts based on constant blower power. Finally, new correlations for predicting heat transfer and friction factor for turbulent flow through a circular tube fitted with the inserts were proposed.